COMMUNICATIVE LANGUAGE TEACHING APPROACH (A CRITICAL ANALYSIS) - Asmawati, Nur (Hunafa: Jurnal Studia Islamika, 2005)
Communicative approach is one of the language teaching approaches used in improving learnerâs language skill. It is one of the alternative approaches in the language teaching and learning processes which can help create positive atmosphere in the learning of language in general and learning English in particular. Applying this approach, language teacher and learner can participate actively in various classroom activities. It can give as many opportunities as possible to language learners to interact among themselves and to express their ideas in English.It is within the above context that this article aims at offering communicative approach to the teaching and learning of English in Indonesia.Key Words: Communicative, Language, Teaching, Approach